A legume-enriched diet improves metabolic health in prediabetes mediated through gut microbiome: a randomized controlled trial - Xiaorong Wu; Alvin Surya Tjahyo; Vera Sergeyevna Brok Volchanskaya; Long Hui Wong; Xianning Lai; Yi Ning Yong; Farhana Osman; Shia Lyn Tay; Priya Govindharajulu; Shalini Ponnalagu; Rachel Tso; Hwee Sze Teo; et al. (Nature Communications)
Abstract Healthy dietary patterns rich in legumes can improve metabolic health, although their additional benefits in conjunction with calorie restriction have not been well-established. We investigated effects of a calorie-restricted, legume-enriched, multicomponent intervention diet compared with a calorie-restricted control diet in 127 Chinese prediabetes participants, living in Singapore. The study was a 16-week, single-blind, parallel-design, randomized controlled trial (n = 63 intervention group (IG), n = 64 control group (CG); mean ± SD age 62.2 ± 6.3 years, BMI 23.8 ± 2.6 kg/m2). Primary outcomes were markers of glycemia and all measurements were taken at 2 or 4-weekly intervals. At the end of 16 weeks, both groups had significantly lower BMI (q (Time) = 1.92 ×10-42, β  = -0.02) compared with baseline, with minimal difference between groups. The IG had significantly greater reductions in LDL cholesterol (q (Treatment×Time) = 0.01, β  = -0.16), total cholesterol (q (Treatment×Time) = 0.02, β  = -0.3) and HbA1c (q (Treatment×Time) = 0.04, β  = -0.004) compared with CG, alongside increases in fiber degrading species in IG, mediated through metabolites such as bile acids and amino acids. A legume-enriched, multicomponent intervention diet can improve metabolic health in a prediabetes population, in addition to benefits obtained from calorie restriction alone, partially mediated through changes in gut microbial composition and function. Trial registration: Clinical Trials NCT04745702.